Studi Komparatif Terhadap Interpretasi Khamar Perspektif Kiai Haji Shaleh Darat Dan Kiai Haji Daud Ismail - Bahruddin, Bahruddin (Journal Education And Islamic Studies, 2023)
Khamar is an intoxicating drink that has existed since Islam developed in the Arabs, even the Prophet Muhammad SAW once conveyed the prohibition of drinking alcohol, because it has a negative impact on the state of the body and health. The purpose of this study is to increase understanding related to the verses of khamar in Surah Al-Maidah: 90. This research is a library research using qualitative methods. This research explains the understanding of the verse of alcohol in the perspective of the book of interpretation Faid al-Rahman fi Tarjamah Tafsir Kalam Malik al-Dayyan by kiai haji Shaleh Darat and Kitab tafsir Al-Munir by kiai haji Daud Ismail. The results of this study can be concluded, that in both books of interpretation have the same view of the status of the prohibition of alcohol, but actually if a deeper study is done we will find a number of differences from certain aspects in their interpretation. for example, at the beginning of the interpretation, Kiai haji Saleh Darat began to interpret this verse by explaining khamar according to the interpretation of the dzahir verse without mentioning other forms of khamar itself. According to Kiai Haji Daud Ismail, he began to interpret zahir by applying elements of locality in interpreting the Qur'an to make it easier for readers to understand the messages in the Qur'an. Unlike the interpretation of Kiai Daud Ismail which has legal nuances, the interpretation of Kiai Shaleh is more sufistic or Sufism. Meanwhile, according to kiai Shaleh Darat interpreting al-Maidah verse 90 is based on the signals he received. namely he divides khamar into two kinds, there is khamar dzahir and there is batin khamar.